MOTIVATION FOR TEACHING AND ITS CORRELATIONS WITH INTENTIONS TO TEACH OF SENIOR STUDENTS AT FELTE-ULIS-VNU = ĐỘNG LỰC DẠY VÀ MỐI LIÊN HỆ VỚI Ý ĐỊNH DẠY CỦA SINH VIÊN NĂM 4 KHOA SƯ PHẠM ANH-ĐẠI HỌC NGOẠI NGỮ-ĐHQGHN - Trần, Thị Hồng Duyên (2020)
Recent years have witnessed a decrease in the number as well as the quality of students enrolling in Teacher Education programs, including English Language Teaching. Those who graduate from English Language Teacher Education programs also tend to pursue careers other than teaching. Given the great demand for English and English language learning at the moment, such low motivation for teaching is obviously undesirable. The current study thus was conducted with the aim of investigating the intentions to teach of senior students at FELTE-ULIS-VNU, the factors influencing their choices of a teaching career as well as the relations of these two matters. The data was collected using questionnaire method with the participation of 114 senior students at FELTE-ULIS-VNU and analyzed using quantitative data analysis method. Findings from the study suggested that the majority of participants displayed a positive prospect of pursuing teaching career while the rest showed little thought of becoming teachers. Prior teaching and learning experience, make social contribution, and shape future of children/adolescents were rated as the most influential teaching motivations while fallback career, job transferability, and time for family were found to be the least endorsed ones. Additionally, results from this study also revealed that although Vietnamese teachers are perceived to be part of a respected profession that requires expert knowledge and emotional demand, they are generally underpaid. Correlational analysis suggested significant relations between intrinsic career value, satisfaction with choice, social utility values, perceived ability, and prior teaching and learning experience and intentions to teach. The need to create a positive image of effective teachers was proposed due to its benefits in promoting the highly-rated motivations for teaching among students.